Reparative Regeneration by Substitution of Bone Tissue Defects with Bioglass, Using Regeneration Technologies - Buryanov,Olexander A (Sociedad Chilena de Anatomía, 2021)
SUMMARY: Bioactive glass (BG) induces osteogenesis of damaged bone, causing excessive bone formation. This study included a morphological and morphometrical data of the bone tissue regeneration by filling bone defects with BG with autologous native platelet rich plasma (PRP) or fibrin (PRF) and aspirate of bone marrow (ABM). The parameters of newly formed bone in rabbits bone defect were analyzed and compared with terms 4th and 12th week. The groups with ABM-BG, PRF-BG and PRP-BG have shown common tendency: development of newly formed bone tissue, the external contour of the bone has been enlarged; an additional trabecular bone has been formed under the cortical layer, which has often been limited by a solid compact bone from the bone marrow. The induced osteogenesis resulted in the appearance of a significant amount of bone tissue exceeding the original size of the defect. Increased density of the newly formed tissue at the defect level relative to ABM-BG was detected in the PRF-BG group at 12 weeks and PRP-BG at 4 and 12 weeks (p<0.05). In this case, the bone thickness in the substituted defect was greater in the ABM-BG group. The number of newly formed bone tissue in the ABM-BG group at 4 weeks also exceeded the value of the BG group, but the density of such bone did not differ between the groups. That is, ABM-BG stimulated greater trabecular bone formation and fibrous reticular tissue was located in the lacunae between trabeculae. These results indicate that the additional use of tissue technology (ABM, platelet plasma) facilitated osteogenesis, and the newly formed bone tissue was tightly coupled and remodeled to the cortical bone layer in the form of compact bone tissue. PRP, to a greater extent than ABM, promoted the formation of compact bone tissue.